Being and «genera» of being in Ancient Stoicism. A relevant ontological distinction applied to ethics and action theory - Boeri, Marcelo D. (Pensamiento. Revista de Investigación e Información Filosófica, 2014)
This paper is focused on the Stoic doctrine of genera of being and the way in which such a doctrine appears to function in ethics and in action theory. In section I, the soul-body problem in Aristotle is briefly discussed; I argue that, in order to overcome the difficulties of the relation between soul and body in a psychology maintaining that the soul is an immaterial entity, the Stoics were willing to endorse a physicalist psychology. Second, I offer an account of the Stoic ontology and attempt to show the role of each genera of being in such an ontology. In section III I return to the Stoic genera of being but concentrating on the suitable connections to make more persuasive the thesis that the Stoic genera of being should play a role in ethics and in action theory. Finally, in section IV I present some concluding remarks.
Keywords: genera of being; categories; Stoicism